(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Helicobacter pylori (H. pylori) infection is generally procured in youth. H. pylori infection isrelated with a few upper gastrointestinal problems. Neighborhood information on the study of diseasetransmission of the infection are scant in Palestine. study on incidence of h. pylori infection The reasonfor this study is to quantify the rate and to investigate the related variables among the population living inGaza strip. Helicobacter pylori are a gram negative, winding molded microearophilic bacterium, it wasfound in around 66 of the total populace